Novel Approaches for Single Molecule Activation and Detection - Benfenati, Fabio; Di Fabrizio, Enzo; Torre, Vincent (Advances in Atom and Single Molecule Machines,, 2014)
How can we obtain tools able to process and exchange information at the molecular scale? In order to do this, it is necessary to activate and detect single molecules under controlled conditions. This book focuses on the generation of biologically-inspired molecular devices. These devices are based on the developments of new photonic tools able to activate and stimulate single molecule machines. Additionally, new light sensitive molecules can be selectively activated by photonic tools. These technological innovations will provide a way to control activation of single light-sensitive molecules, allowing the investigation of molecular computation in a biological environment.